2019
DOI: 10.1007/s40093-019-00297-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-production and biomass yield of amaranthus (Amaranthus hybridus) and tilapia (Oreochromis niloticus) in gravel-based substrate filter aquaponic

Abstract: Purpose Aquaponics combine aquaculture with crop production in a mutual system. In this experiment, the growth of Amaranthus in aquaponics with tilapia fish was investigated. Methods 500-liter water tanks containing tilapia fish at four initial stocking densities of 100, 150, 200, and 250 fish/m 3 were used in triplicates, with a view to evaluate vegetable yields as influenced by fish biomass to water ratio. 1 g of Amaranthus seeds were sown in a 1 m 2 planting trough, which contained gravel with a top layer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Increasing the volume of the fish production tanks from 500 to 1000 L while maintaining the fish density (12 fish/m 3 -4 kg/m 3 ) and the volume of the vegetable growing bed (500 L) did not improve the performance of the fish, which was possibly due to the maintenance of the water quality and of the fish stocking density. The effect of Nile tilapia density in gravel aquaponic system on performance was demonstrated by Babatunde et al (2019), who found a decrease in final weight (57.5 to 42.0 g), weight gain (43.2 to 34.0 g) and daily weight gain (1.0 to 0.79 g/day) as density was increased from 100 fish/m 3 (5.7 kg/m 3 ) to 250 fish/m 3 (10.0 kg/m 3 ). The performance results obtained in the present study are adequate, considering values obtained with Nile tilapia in net-tanks (Moraes et al, 2009) (biomass gain: 0.476 kg; feed conversion: 1.59), in fish ponds (Assano et al, 2011) (daily weight gain: 2.37 g/day; feed conversion: 1.3) and in aquaponics with biofloc technology (BFT) (Lima et al, 2015) (daily weight gain: 2.16 to 2.36 g/day; feed conversion: 1.38 to 1.62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the volume of the fish production tanks from 500 to 1000 L while maintaining the fish density (12 fish/m 3 -4 kg/m 3 ) and the volume of the vegetable growing bed (500 L) did not improve the performance of the fish, which was possibly due to the maintenance of the water quality and of the fish stocking density. The effect of Nile tilapia density in gravel aquaponic system on performance was demonstrated by Babatunde et al (2019), who found a decrease in final weight (57.5 to 42.0 g), weight gain (43.2 to 34.0 g) and daily weight gain (1.0 to 0.79 g/day) as density was increased from 100 fish/m 3 (5.7 kg/m 3 ) to 250 fish/m 3 (10.0 kg/m 3 ). The performance results obtained in the present study are adequate, considering values obtained with Nile tilapia in net-tanks (Moraes et al, 2009) (biomass gain: 0.476 kg; feed conversion: 1.59), in fish ponds (Assano et al, 2011) (daily weight gain: 2.37 g/day; feed conversion: 1.3) and in aquaponics with biofloc technology (BFT) (Lima et al, 2015) (daily weight gain: 2.16 to 2.36 g/day; feed conversion: 1.38 to 1.62).…”
Section: Discussionmentioning
confidence: 99%
“…Good performance results have been obtained for vegetables and fish, such as tilapia, in gravel aquaponic systems at different stocking densities (Babatunde et al, 2019), and better biomass gain and yield results were achieved as compared with the NFT and raft systems (Lennard and Leonard, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tanjung et al (2019) reported that the best pH for tilapia was 7.0-7.4. The pH values for each treatment in this study were also suitable for the nitrification process (Trang et al, 2017;Babatunde et al, 2019). Wambua et al (2018) stated that the pH value of water is directly proportional to the temperature and the toxicity level of ammonia in the water.…”
Section: Water Qualitymentioning
confidence: 93%
“…Ingeniería Solidaria Table 5 shows the most commonly used species combinations together with the type of hydroponic system, reported yields and fish-plant ratios recommended by authors. Water flow is generally continuous, although flow rate varies depending on the specific dimensions of each system [48], as feed consumption and waste production may change depending on these.…”
Section: Yield and Water Usementioning
confidence: 99%